Activity Level and Type During Post-acute Stages of Concussion May Play an Important Role in Improving Symptoms Among an Active Duty Military Population - Remigio-Baker, Rosemay A.; Bailie, Jason M.; Gregory, Emma; Cole, Wesley R.; McCulloch, Karen L.; Cecchini, Amy; Stuessi, Keith; Andrews, Taylor R.; Qashu, Felicia; Mullins, Lynita; Sargent, Paul; Ettenhofer, Mark L. (Frontiers in Neurology, 2019)
Background: Previous research demonstrates that early rest and gradual increases in activity after concussion can improve symptoms; however, little is known about the intensity and type of activity during post-acute time periods –specifically months post-injury– that may promote optimal recovery in an active duty service member (SM) population. Objective: The objectives of this study were to investigate how activity level and type at the post-acute stages of concussion (at 1 and 3 month[s] post-injury) impact subsequent symptoms among SMs, and how this relationship might differ by the level of symptoms at the time of injury. Methods: Participants included 39 SMs ages 19-44 years from 3 military installations who were enrolled within 72 hours after sustaining a concussion. Linear regression was used to evaluate whether the association between activity level at 1 or 3 month[s] post-injury (as measured by a multi-domain Activity Questionnaire) and subsequent symptoms at 3 and/or 6 months (as measured by the Neurobehavioral Symptom Inventory) varied by the level of symptoms at acute stages of concussion. Partial correlation was used to evaluate relationships that did not differ by acute symptom level. Symptoms at the time of activity assessment (1 or 3 month[s]) were accounted for in all models, as well as activity level at acute stages of concussion. Results: Greater physical and vestibular/balance activity at 1 month were significantly correlated with lower symptoms at 3 months, but not at 6 months post-injury. There were no significant associations found between activity (total or by type) at 3 months and symptoms at 6 months. The association between activity level at either 1 or 3 months and subsequent symptoms at 3 and/or 6 months did not differ by the level of acute symptoms. Conclusion: The intensity and type of activities in which SMs engage at post-acute stages of concussion may impact symptom recovery. Although low levels of activity have been previously shown to be beneficial during the acute stage of injury, higher levels of activity may provide benefit at later stages. These findings provide support for the importance of monitoring and managing activity level beyond the acute stage of concussion.